EFFECT OF SOME SUNFLOWER (Helianthus annuus L) GENOTYPES OIL ON SOME PATHOGENIC BACTERIAL SPECIES - Al-Shamma, Laith; Bu-risha, Rasmiya; Al-Shamma, Nawal; K, Batol (Iraqi Journal of Science, 2024)
The effect of seed oil of four sunflower genotypes on some of pathogenic bacteria were studied Using sunflower Manon, Pan7392, Euroflor and Sen Altheep at different concentration100,75,50 and 25%. pathogenic bacteria was Isolated from Al_yarmok hospital Baghdad included Escherichia coli, Pseudomonas aeruginosa , Staphylococcus aureus, Klebsiella pneumoniae and Streptococcus pyogenes .Oil of Euroflor genotype had more inhibition on all pathogenic bacteria in all using different concentration . E. coli bacteria was more sensitive then other pathogenic bacteria .Interaction between oils and pathogenic bacteria was significant, some results were also observed when Euroflor oil was used against E. coli in all concentration used, the diameter of inhibition was (7,8,18and 10mm) respectively and S. aureus , K. pneumoniae of concentration 50% of diameter inhibition15mm and diameter 8mm at concentration. In oil inhibited E. coli bacteria with diameter inhibition 8mm and no significant with Euroflor genotype, was observed.